Sao Tome and Principe : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report, 2008)
Sao Tome and Principe's economy is heavily dependent on the international economy. The study assessed the country's macroeconomic, structural, and social policies in support of growth and poverty reduction. The implementation of the National poverty reduction strategy (NPRS) through People's Action Party (PAP) made some progress with the help of reforms implemented through government incentives. PAP envisages political measures, legislative and regulatory actions, restructuring and reorganization of government agencies, and Public Investment Program (PIP) for the different pillars of the NPRS. The study assessed that successful implementation of NPRS requires stability, real ownership of NPRS, and consistency between PIP and PAP.